The Effects Of Liquidity, Solvency, Type Of Industry, And Auditor Switching On Audit Report Lag In Lq45 Index Companies - Sylvia Fettry; Kheren Yutinsia Hersan (Kesatuan Press, 2020)
Financial statement should provide high quality of information which is useful for stakeholder, especially investors to make investment decision. The important quality of a financial statement is timeliness. Otoritas Jasa Keuangan (OJK) has regulated that go public companies have to provide annual financial statement along with the audit report from public accountant that must be given to OJK not later than the end of third month after the financial year ends. Therefore, it is important for companies to pay attention in audit report lag. This research is focused on the effect of liquidity, solvability, type of industry and auditor switching toward audit report lag. This research is conducted at LQ45 Index Companies which are listed on Indonesia Stock Exchange in 2015 – 2018. The research method is causal study. The hypothesis is testing using panel data regression. This research founds that type of industry has a significant partial effect on audit report lag. Whereas, liquidity, solvability and auditor switching do not have significant partial effect on audit report lag. Furthermore, on simultaneous test, it is founded that liquidity, solvability, type of industry and auditor switching are simultaneously affecting audit report lag.